PENGEMBANGAN MEDIA PEMBELAJARAN INTERAKTIF BERBASIS POWERPOINT UNTUK MENINGKATKAN KEMAMPUAN PEMAHAMAN MATEMATIS SISWA TUNAGRAHITA KELAS VIII SLB C YAKUT PURWOKERTO - Afifa Nur Fauziyyah; Fitria Zana Kumala (Universitas Muhammadiyah Semarang, 2024)
Students that possess mathematical comprehension ability are able to reason rationally and solve difficulties in both ordinary life and mathematical contexts. Low comprehension skills are exhibited by SLB C Yakut Purwokerto students with modest intellectual impairments. This is a result of the continued use of traditional learning materials, which makes learning challenging for kids. As a result, learning media play a crucial role in education. Students will be more motivated to participate in learning to enhance their mathematics comprehension skills when they are exposed to high-quality learning materials. Thus, the goal of this project is to create interactive learning materials based on PowerPoint that are reliable and efficient for enhancing mathematical comprehension. Research and Development (R&D) is the research methodology employed. With a proportion of material expert validation of 80%, media expert validation of 82.5%, trials by math instructors of 86%, and field trials of 91.3%, the research's findings demonstrate that the media produced is legitimate and appropriate for usage. In addition, interactive learning materials based on PowerPoint were shown to be successful, with the experimental class outperforming the control group in terms of N-Gain. The experimental class's N-Gain score was 77.1%, compared to only 23.8% for the control group. This research concludes that PowerPoint-based interactive media is effective in improving mathematical understanding of students with intellectual disabilities.